2010
DOI: 10.5152/eajm.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Incidence in Erzurum City

Abstract: Objective: Known as an uncommon disease at the beginning of the 20 th century, lung cancer has been the most frequent cause of cancer-related deaths in males since the 1950s and in females in the last two decades. The aim of this study was to determine the lung cancer incidence in Erzurum; its clinical properties, cancer subtypes, and application phases; the relationships of tumors with parameters of cigarette smoking and nutrition; radiological properties of the tumors; and the methods of diagnosis. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In Japan the ratio is 2.8/1 (Kanematsu et al, 2010). In a study in 2010, 255 patients diagnosed with lung cancer in 2005, 220 of whom (86.3%) were male and 35 were female (13.7%) are evaluated in Erzurum (Araz et al, 2010). The ratio in our region was 6/1 in 2005.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…In Japan the ratio is 2.8/1 (Kanematsu et al, 2010). In a study in 2010, 255 patients diagnosed with lung cancer in 2005, 220 of whom (86.3%) were male and 35 were female (13.7%) are evaluated in Erzurum (Araz et al, 2010). The ratio in our region was 6/1 in 2005.…”
mentioning
confidence: 61%
“…Recent studies about epidemiology of lung cancer have showed that disease continues to be diagnosed considerably more in men than women (Araz et al, 2010;Kanematsu et al, 2010;Dey et al, 2012). When the minor variations excluded, lung cancer is the most frequent cancer among men and the second most common cancer among women in the World, including Turkey (Araz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeterminate lesions are still one of the most challenging problems in current clinical practice. In such cases, computerized tomography (CT) serves as the standard of reference and its use is recommended for the evaluation of these nodules in the current guidelines [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Although magnetic resonance imaging (MRI) is not used as a first choice in the evaluation of indeterminate nodules, the advantages of using dynamic MRI for tumor catheterization have been demonstrated in several studies [ 9 , 10 ], and due to technical improvements MRI has gained importance for tumor detection and interpretation [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%